Muscle-Type Nicotinic Receptor Modulation by 2,6-Dimethylaniline, a Molecule Resembling the Hydrophobic Moiety of Lidocaine - Alberola-Die, Armando; Fernández-Ballester, Gregorio; González-Ros, José M.; Ivorra, Isabel; Morales, Andrés (Frontiers in Molecular Neuroscience, 2016)
To identify the molecular determinants responsible for lidocaine blockade of muscle-type nAChRs, we have studied the effects on this receptor of 2,6-dimethylaniline (DMA), which resembles lidocaine’s hydrophobic moiety. Torpedo marmorata nAChRs were microtransplanted to Xenopus oocytes and currents elicited by ACh (IACh), either alone or co-applied with DMA, were recorded. DMA reversibly blocked IACh and, similarly to lidocaine, exerted a closed-channel blockade, as evidenced by the enhancement of IACh blockade when DMA was pre-applied before its co-application with ACh, and hastened IACh decay. However, there were marked differences among its mechanisms of nAChR inhibition and those mediated by either the entire lidocaine molecule or diethylamine (DEA), a small amine resembling lidocaine’s hydrophilic moiety. Thereby, the IC50 for DMA, estimated from the dose-inhibition curve, was in the millimolar range, which is one order of magnitude higher than that for either DEA or lidocaine. Besides, nAChR blockade by DMA was voltage-independent in contrast to the increase of IACh inhibition at negative potentials caused by the more polar lidocaine or DEA molecules. Accordingly, virtual docking assays of DMA on nAChRs showed that this molecule binds predominantly at intersubunit crevices of the transmembrane-spanning domain, but also at the extracellular domain. Furthermore, DMA interacted with residues inside the channel pore, although only in the open-channel conformation. Interestingly, co-application of ACh with DEA and DMA, at their IC50s, had additive inhibitory effects on IACh and the extent of blockade was similar to that predicted by the allotopic model of interaction, suggesting that DEA and DMA bind to nAChRs at different loci. These results indicate that DMA mainly mimics the low potency and non-competitive actions of lidocaine on nAChRs, as opposed to the high potency and voltage-dependent block by lidocaine, which is emulated by the hydrophilic DEA. Furthermore, it is pointed out that the hydrophobic (DMA) and hydrophilic (DEA) moieties of the lidocaine molecule act differently on nAChRs and that their separate actions taken together account for most of the inhibitory effects of the whole lidocaine molecule on nAChRs.